(untitled) (Modern education and development, 2025)
This article analyzes the aesthetic and philosophical views of Alexander Feinberg in literature. The main philosophical ideas put forward in his works, his approach to the problems of man and society, and the specific aspects of his poetic thinking are studied. The reflection of truth, justice, spiritual perfection, and national values ​​in his work is also analyzed. How aesthetic ideals and artistic methods of depiction are expressed in Feinberg’s poetry is also considered. The article reveals Feinberg’s place in the modern literary process and highlights the significance of his creative heritage for today and future generations. Ushbu maqolada Aleksandr Faynbergning adabiyotdagi estetik va falsafiy qarashlari tahlil qilinadi. Uning asarlarida ilgari surilgan asosiy falsafiy g‘oyalar, inson va jamiyat muammolariga yondashuvi hamda poetik tafakkurining o‘ziga xos jihatlari o‘rganiladi. Shuningdek, uning ijodida haqiqat, adolat, ma’naviy kamolot va milliy qadriyatlarning aks etishi tahlil qilinadi. Faynbergning she’riyatida estetik ideal va badiiy tasvir uslublari qanday ifodalanganligi ham ko‘rib chiqiladi. Maqola, Faynbergning zamonaviy adabiy jarayondagi o‘rnini ochib berib, uning ijodiy merosining bugungi va kelajak avlod uchun qanday ahamiyatga ega ekanini yoritadi. В данной статье анализируются эстетические и философские взгляды Александра Фейнберга в литературе. Изучены основные философские идеи, выдвинутые в его произведениях, его подход к проблемам человека и общества, специфические стороны его поэтического мышления. Также анализируется отражение истины, справедливости, духовной зрелости и национальных ценностей в его творчестве. Также рассматривается способ выражения эстетических идеалов и стилей художественного образа в поэзии Файнберга. В статье раскрывается место Фейнберга в современном литературном процессе и подчеркивается значение его творческого наследия для сегодняшнего и будущих поколений.